Investigating the Effectiveness of the Self-Esteem Educational Package in Elementary School Students - Mahdieh Heidarizad; Masoud Janbozorgi (تربیت اسلامی, 2022)
This study was conducted to investigate the effectiveness of the self-esteem educational package in elementary school students. For this purpose, through the available sampling method, 16 out of 43 students in grade three were selected three according to the inclusion criteria. The subjects were randomly divided into two groups and subjected to the Rosenberg’s self-esteem scale. The subject group of the study, in addition to their usual training, was trained twice a week in their self-esteem program, which was prepared by the author and its validity was confirmed by the experts. The control group followed their usual training and after eight sessions of training to the subject group, the mentioned tests were taken again from the two groups and the data were analyzed by the covariance analysis method. The 20th edition of SPSS software and one-way analysis of covariance test were used to analyze the data. The findings showed that, compared to the control group, the subjects’ scores in the self-esteem variable had increased significantly (P<0.05). As a whole, the findings indicated that the application of the self-esteem training program on elementary school students could result in an increase in self-esteem.